Parotid tumors - Casuistry of the last 10 years of the Otolaryngology Department of Lisbon IPO - Oliveira, Filipa (2013)
The salivary gland tumors are uncommon neoplasms of the head and neck region, corresponding to 3-5% of the tumors in this location. In this article we will be doing a retrospective study of the occurrence of tumors of the parotid gland over the past 10 years in the Department of Otorhinolaryngology IPO Lisbon. Data were collected from a total of 153 patients from the period of 1st January of 2001 to 31st December of 2011 and was evaluated the incidence of the various subtypes of tumors, treatment given and the follow-up of patients. We also took into account the possible complications, recurrences and complementary treatments. We have concluded that, as in the bibliography, these tumors are rare and mostly benign, having a proportional ratio between the size of the salivary gland and benign tumor. The treatment of choice for the parotid gland neoplasm is surgery, regardless of whether it is a benign or malignant tumor, since there is a steady growth of tumor and its malignant potential.